The Subgenus-Specific C-Terminal Region of Protein IX Is Located on the Surface of the Adenovirus Capsid - Akalu, Abebe (American Society for Microbiology, 1999)
We have investigated the antigenicity of the C- and N-terminal halves of pIX of human adenovirus types 2 and 3 (Ad2 and Ad3) as well as their orientations in virions. We found that only the C-terminal halves of Ad2 pIX and Ad3 pIX reacted in a subgenus-specific manner by enzyme-linked immunosorbent assay and immunoblot analysis. Based on immunoelectron microscopy experiments, pIX in viral capsids appears to be positioned such that the C-terminal part of pIX constitutes the surface domain whereas the N terminus of the protein makes up the internal domain in icosahedral Ad capsids.